STUDY OF GOLDFISH (Cyprinus carpio) BABY CHIPS USING DIFFERENT TYPES OF FLOUR ON CONSUMER ACCEPTANCE - Arbian, Rendi; ', Suparmi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to determine the using of flour as a binder for goldfish baby chips with appearance, aroma, texture and flavour on consumer acceptance. The treatment for this research was adding of flour, T0 (300 gr rice flour + 100 gr wheat flour), T1 (300 gr rice flour + 100 gr tapioca) and T2 (300 gr rice flour + 100 gr sagoo flour). The parameters was observed for organoleptic test, the crispness and proximate analysis on goldfish baby chips. The result showed that goldfish baby chips with the formulation of rice flour and tapioca flour was most preferable by consumer acceptance, with water content 25.69%, ash content 3.72%, fat content 11.19%, protein content 34.62% and crispness value 3.50.Keywords: Consumer acceptance, Fish baby chips, flour, goldfish.